Saluran Distribusi Pemasaran Komoditi Jahe Merah Di Pasar Karombasan Kota Manado - Pasuhuk, Maryane Tasya; Kaunang, Rine; Rori, Yolanda Pinky Ivanna (Sam Ratulangi University, 2023)
This study aims to determine the red ginger commodity marketing distribution channel at Karombasan Market, Manado City. This research was conducted from September to October 2022. The selection of respondents was carried out using the Snowball Sampling technique. The data used are primary data and secondary data. Primary data was collected through interviews and direct observation with wholesalers, retailers and consumers at the Karombasan Market based on a questionnaire. So that the total respondents were 10 people. Secondary data was obtained from the Karombasan Market office, regarding the history of the Market, regional boundaries, and the structure of the Market management. Secondary data was also obtained from the internet via Google Scholar in the form of books, journal articles and theses related to the topic of this research. The method of data analysis is descriptive qualitative analysis. The results showed that the assessment of marketing distribution channels at the Karombasan Market consisted of 1 channel, farmers - wholesalers - retailers - consumers. Wholesalers buy red ginger to farmers from Bolaang Mongondow and South Minahasa areas as much as 1,000 kg. Wholesalers sell red ginger to retailers at a price of IDR10,000 per Kg and retailers sell red ginger to consumers at a price of IDR12,000 per Kg. The linkage of marketing institutions in each red ginger distribution process forms 3 streams, product flow, information flow, and financial flow.